Aluminum-carbon metal matrix composites for fasteners

By adding carbon nanotubes to aluminum matrix composites and processing them, the problem of insufficient thermal stability and creep resistance of fasteners in high temperature and electrical applications is solved, improving their strength and electrical conductivity, reducing their strength and electrical conductivity The risk of failure when bonding with different metals provides a more reliable electrical connection.

CN119301817APending Publication Date: 2025-01-10YAZAKI CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380045141.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing fasteners have insufficient thermal stability and creep resistance in high temperature and electrical applications, and when engaged with different metals, they are prone to loose connection problems caused by galvanic corrosion and thermal expansion differences, which affects the reliability of the electrical system.

Method used

Using aluminum matrix composite material (MMC) fasteners, by adding nanostructured materials such as carbon nanotubes (CNTs) to aluminum, the uniform distribution and mechanical strengthening of carbon nanotubes are achieved through extrusion, cold processing and annealing, and the uniform distribution and mechanical strengthening of carbon nanotubes are improved. The strength, thermal stability and electrical conductivity of the fastener.

Benefits of technology

The high strength, excellent thermal stability and electrical properties of aluminum matrix composite fasteners are achieved, reducing the risk of failure when bonding with different metals, and providing more reliable and safe electrical connections for high temperature and electrical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301817A_ABST
    Figure CN119301817A_ABST
Patent Text Reader

Abstract

A fastener configured for power distribution applications is disclosed. The fastener comprises an aluminum (Al) metal matrix composite (MMC) comprising nanoscale carbon particles at a concentration of 0.01 wt% to 2 wt%. And the nanoscale carbon particles are uniformly distributed in the whole MMC. The fasteners may be used to connect conductors, such as busbars, wires, or cables. A method for manufacturing an aluminum MMC fastener is also disclosed, the method including a solid state deformation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The teachings disclosed herein relate to metal composite materials for use in fasteners. Background Art

[0002] A fastener is a hardware device that mechanically joins or secures two or more objects together. Typically, fasteners are used to create non-permanent joints; that is, joints that can be removed or disassembled without damaging the joined parts. Welding is an example of creating a permanent joint. Steel fasteners are typically made of stainless steel, carbon steel, or alloy steel.

[0003] Other alternative methods of joining materials include crimping, welding, soldering, brazing, taping, gluing, adhesive bonding or using other adhesives. Force may also be used, such as with magnets, vacuum (e.g., suction cups), or even friction (e.g., tacky pads). Some types of woodworking joints use separate internal reinforcements, such as dowels or pins, which in a sense can be considered fasteners within the scope of the joining system, although they are not general fasteners themselves. BRIEF DESCRIPTION OF THE DRAWINGS

[0004] One or more embodiments of the present disclosure are illustrated by way of example and not limitation in the figures of the accompanying drawings in which like reference numerals refer to similar elements.

[0005] Figure 1 An exemplary process flow diagram for metal matrix composite (MMC) fastener preparation is shown.

[0006] Figure 2 A general diagram of one type of fastener is shown.

[0007] Figure 3 is a graph showing the beneficial physical properties of aluminum (Al) with 0.5 weight % (wt %) carbon nanotubes (CNTs) in an extruded state, and Al with 0.75 wt % CNTs in an extruded and drawn state, compared to the properties of pure aluminum.

[0008] Figure 4 is a graph showing creep test results for Al 0.75 wt% CNT samples compared to results for pure Al (Al99.7) and Al 6000 series alloy samples.

[0009] Figure 5 is a graph showing how cold working affects the strength of Al-0.5wt% CNT MMC wires compared to the strength of pure Al wires.

[0010] Figure 6is a graph showing the results of thermal stability testing on drawn Al-0.5wt% CNT wires with two different levels of applied cold work (area reduction 85% and 98%).

[0011] Figure 7 is a picture showing the improvement of carbon nanotube (CNT) distribution using solid-state reprocessing.

[0012] Figure 8 Included is an image of a unique grain electron backscatter diffraction (EBSD) pattern demonstrating the beneficial effect of uniform CNT distribution in the as-pulled Al 0.5wt% CNT MMC wire.

[0013] Fig. 9 Included is a graph comparing the thermal stability of a drawn Al-0.5 wt% CNT MMC wire with poor CNT distribution and a drawn Al-0.5 wt% CNT MMC wire with a more homogenous CNT distribution.

[0014] Fig. 10A and Fig. 10B Shown is a test setup for simulation of an electrical bus-to-busbar connection using Al-CNT MMC fasteners to connect the busbars.

[0015] Fig.11 is a graph showing a comparison of pre-tension loss in a busbar-to-busbar connection for an aluminum busbar combined with stainless steel fasteners versus a connection consisting of an Al-CNT MMC busbar with Al-CNT MMC fasteners.

[0016] By studying the specific embodiments in conjunction with the accompanying drawings, the various features of the embodiments described herein will become more apparent to those skilled in the art. The embodiments are shown in the accompanying drawings by way of example and not limitation, and similar reference numerals may indicate similar elements in the accompanying drawings. Although the accompanying drawings depict various embodiments for illustrative purposes, it will be appreciated by those skilled in the art that alternative embodiments may be employed without departing from the principles of the disclosed technology. Therefore, although specific embodiments are shown in the accompanying drawings, the present technology is susceptible to various modifications. DETAILED DESCRIPTION

[0017] The disclosed technology relates to a technology for preparing aluminum (Al)-based metal matrix composite (MMC) fasteners having desired strength, thermal stability and creep resistance without significantly reducing electrical conductivity below that of pure Al. It is beneficial to create a fine dispersion of reinforcing particles surrounded by an α-Al matrix that is relatively lacking in solute atoms. To achieve this result, a metal matrix composite (MMC) additive that has no significant solubility in α-Al is used. Since carbon has no reported solid solubility in Al and exists in a variety of nanoparticle forms (e.g., nanoscale structures such as carbon nanotubes (CNTs), which can be single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs), graphene nanosheets (GNPs), fullerenes, nanodiamonds), it is an ideal candidate as an additive for Al-based MMC fasteners for power distribution applications.

[0018] In an embodiment, the reinforcing particles include carbon in the form of carbon nanotubes (CNTs). The CNTs may be single-walled CNTs, multi-walled CNTs, or a combination of both types.

[0019] In another embodiment, the reinforcing particles include carbon in the form of graphene nanoplatelets (GNPs), fullerenes, nanodiamonds, or any combination thereof.

[0020] In another embodiment, the strengthening particles include mainly sp 2 or sp 3 Hybridized form of carbon. Mainly sp 2 Examples of hybrid carbon include CNTs, GNPs, and fullerenes. 3 Examples of hybrid carbon are nanodiamonds. Amorphous carbon and carbon black are examples of sp 2 and sp 3 Examples of carbon forms that are mixtures of hybrid forms.

[0021] Adding less carbon (C) nanoparticles to Al than Al provides increased tensile strength of Al while maintaining substantially similar conductivity, elastic modulus, and thermal expansion coefficient. For example, a composite product of Al and carbon nanotubes (CNTs) or an "Al-CNT" composite product obtains its tensile strength through processing and dispersion hardening. During cold working by rolling, drawing, or other processes, the grain structure is refined and the CNTs are more evenly dispersed in the matrix. Although the tensile strength of Al-CNTs increases with CNT content, electrical conductivity decreases slightly. From this perspective, a CNT concentration of 0.1wt%-1.0wt% is preferred, which maintains a conductivity of about 60% of the International Annealed Copper Standard (IACS).

[0022] Aluminum 0.5 wt% CNT extrusion products have shown higher strength and heat resistance compared to standard Al conductors, while showing conductivity similar to 1000 series aluminum (60.8% IACS). Strengths in excess of 200 MPa and even in excess of 300 MPa have been measured, as well as thermal stability that meets the AT4 grade requirements of IEC 62004 "Heat-resistant aluminum alloy wire for overhead line conductors." The cross-section of the extruded Al-CNT rod is continuously reduced to the desired diameter by cold working (e.g., rolling, drawing) to achieve mechanical strengthening of the Al-CNT composite material by process and dispersion hardening. The present disclosure includes the applicability of process and dispersion hardened Al-CNT rods for the manufacture of Al fasteners suitable for electrical and / or high temperature applications.

[0023] In order to achieve the maximum beneficial effect from nano-scale carbon additives, particles uniformly distributed throughout the MMC should be obtained. According to the desired preparation ratio and the carbon form used, uniform distribution can be achieved in several ways. For example, adding C particles to the Al melt and casting the MMC is a method, but there are challenges, such as surface stretching effect, density difference between C and liquid Al, and the possibility of burning C additives at Al melting temperature. The second method is to use powder metallurgy technology to uniformly mix Al and nano-scale C powders and sinter them together to become solid billets. Finally, the third method involves mechanical mixing of nano-scale C additives into Al substrates by solid-state processing techniques (such as friction stir processing, equal channel angular extrusion (ECAP), extrusion, etc.).

[0024] The desired resulting MMC product has a uniformly distributed carbon particle (e.g., CNT) concentration throughout its volume. That is, there are no significant irregular spaces or irregular vacuum zones between the carbon particles, the carbon particles are not agglomerated (or any agglomeration is negligible), and there are no regions with higher or lower carbon particle concentrations throughout the product volume. The amount of the carbon particles in the matrix is ​​substantially the same as in all parts of the matrix volume, i.e., the carbon particle concentration of no part in the composite material is significantly different from any other part, e.g., greater than 20%, greater than 10%, or preferably greater than 5% difference.

[0025] In one example, the resulting MMC product has a nonporous uniform density. For example, the density may deviate by up to 2% relative to a theoretical composite density, which may be calculated based on the volume of the material, the relative amounts of Al and carbon particles, and their respective densities. The uniform carbon particle concentration of the sample Al-C MMC provides consistent and uniform properties, such as uniform electrical conductance throughout the volume of the MMC product. The uniform distribution of carbon particles in the sample Al-CMMC product may be verified by high-resolution microscopy.

[0026] Regardless of which technique is used to prepare Al-C MMC, the amount of final residual stress from processing will have an impact on the resulting strength and elongation of the MMC. For fastener applications that require significant elongation or thermal stability, care should be taken to achieve a relatively residual stress-free final state. One method of achieving a final state suitable for the application is to anneal the fastener to relieve residual stress after performing any necessary cold working procedures. Another method is to initially prepare an MMC with near-final dimensions and geometry using a process (e.g., extrusion) running at elevated temperatures to limit the incidence of residual stress. If higher strength is required and elongation and thermal stability are less important, introducing residual stress (e.g., by applying cold working) is a viable method to increase strength.

[0027] Fasteners for busbar applications

[0028] Al-C MMCs (e.g., Al-CNT MMCs) have improved properties compared to common Al alloys. Examples of improved properties include higher strength, higher conductivity, higher heat resistance, and greater creep resistance. As fasteners, Al-CMMC materials provide reliable and effective connectors for electrical applications, such as the connection of busbars, battery components, or utility wires.

[0029] As used herein, the term "aluminum-based" may refer to pure Al, Al alloys, or Al-based MMCs. Examples of applications of aluminum-based fasteners are found in the transportation, telecommunications, utilities, and power generation industries. For example, it is increasingly important to efficiently mount and connect electrical components to Al busbars in vehicles. The disclosed embodiments provide a viable solution for fastening aluminum-based busbars to other components in a convenient, consistent, and safe manner. In electric vehicle / hybrid electric vehicle (EV / HEV) battery module assembly connections, connectors should have high strength, conductivity (thermal and electrical conductivity), and thermal stability. The standard current carrying capacity of aluminum is approximately 0.7 A / mm 2 , which is sufficient to connect the battery modules in EV / HEV. The power requirements of EV / HEV continue to increase, so the need for efficient connections is also increasing.

[0030] Conductor grade Al alloys (such as AA 1350) have an electrical conductivity of 61.2% to 61.8% IACS, and their strength is lower than copper (Cu). Adding alloying elements to Al increases strength (e.g., 2xxx, 5xxx, 6xxx, and 7xxx series alloys), but generally reduces conductivity. In addition, aluminum alloys have low thermal stability because the strengthening additives used in commercially available alloys have relatively high mobility in the Al matrix. Therefore, Al alloys are generally not used for applications with temperatures of about 150°C. However, carbon-enhanced aluminum (Al-C) MMCs, such as aluminum-carbon nanotube (Al-CNT) MMCs, can provide high strength and thermal stability without significant electrical conductivity loss.

[0031] Al-CNT MMCs have high specific strength and excellent thermal and electrical properties. The amount and distribution of CNTs in the Al matrix are key parameters for achieving maximum strength of Al-CNT composites. The length of CNTs in Al-CNT MMCs may not affect the strength of the composite; however, the mechanism used to strengthen the composite may vary with the length of the CNTs. Uniform CNT distribution is important for determining certain properties because the tendency of CNTs to form agglomerates has led to some studies in which lower strength was observed for higher CNT contents due to CNT agglomeration. For example, one study observed that 0.1wt% CNTs produced high strength compared to 0.25wt%, 0.5wt%, and 1.0wt% CNTs, which was due to the uniform dispersion of CNTs in 0.1wt% CNT MMCs without agglomeration compared to MMCs with higher CNT contents (≥0.25wt% CNTs). Another study showed that 0.5wt% CNTs in Al-CNT composites resulted in improved mechanical properties compared to 1.0wt% CNTs, due to extensive agglomerate formation in the higher content CNT composites. Therefore, higher CNT concentrations can be considered beneficial as long as the CNTs are uniformly distributed without significant agglomeration.

[0032] Replacing Cu busbars with Al provides significant weight and cost reductions. However, the transition from Cu to Al busbars requires additional changes to compensate for the differences in properties between Al and Cu. For example, Cu busbars are often connected to components via steel fasteners, and differences in thermal expansion coefficients, creep behavior, and galvanic potential make it dangerous to connect Al busbars to steel fasteners. In addition, safe power distribution using Al conductors requires care to avoid dangerous conditions that can lead to hot spots and ultimately failed connections. The two main causes of these failures are (i) galvanic corrosion and (ii) loose connections due to differences in thermal expansion coefficients and creep. Galvanic corrosion occurs between dissimilar metals in the presence of an electrolyte. Al is a strong anode and will corrode strongly when electrically coupled to Cu or stainless steel. Therefore, connecting Cu busbars to Al busbars using stainless steel fasteners can be problematic unless appropriate precautions are taken (use of Ni coatings, shielding the junction from ambient moisture, etc.). These precautions can be cost-prohibitive and can lead to failures if misapplied. Loose connections due to differences in thermal expansion coefficients and creep behavior can lead to failures in Al power distribution systems. In particular, because Al conductors expand and contract more rapidly with temperature changes than the material holding them (e.g., stainless steel fasteners), compressive forces are applied to Al conductors whenever they are heated. Normal use often results in temperature cycling, either through heat generated by resistance in the conductor (Joule heating), changes in environmental conditions, or from components surrounding the conductor, and this cyclic loading / unloading can cause the conductor to deform at the connection. Due to this deformation, less force is applied at elevated temperatures, but there may be no electrical contact or limited electrical contact at lower temperatures.

[0033] The disclosed technology solves the problems associated with joining Al to dissimilar metals. If the number of dissimilar nodes is reduced, the likelihood of failure is reduced. Therefore, all-Al nodes are an attractive option. For example, connecting two Al busbars with an Al bolt and an Al nut avoids the above-mentioned failures. Al alloy fasteners are commercially available, but the disclosed Al-CMMC (e.g., Al-CNT MMC) provides significant advantages over existing alloys in fastener applications. In particular, the disclosed MMC fasteners have improved properties, including higher thermal stability, tensile strength, and electrical conductivity, compared to current Al alloys used in fastener applications.

[0034] Previous Al fasteners were mainly made from 6000 series alloys such as EN AW 6056. These fasteners achieve an ultimate tensile strength (UTS) of up to about 500 MPa, a yield strength of up to 400 MPa, and an elongation of about 7%. The maximum applicable temperature of these fasteners for short durations is about 150°C or 180°C.

[0035] The disclosed embodiments include Al-MMC fasteners having various combinations of properties in the extruded, cold worked, or cold worked and annealed state. The combination of properties includes electrical conductivity, UTS, and elongation less than, equal to, or greater than specified values.

[0036] In an embodiment, the Al-C MMC fastener has an electrical conductivity greater than about 50% IACS, a UTS greater than about 80 MPa, and an elongation greater than about 30%. Fasteners having such properties may be in an extruded state or a lightly cold worked state, or a cold worked and annealed state.

[0037] In another embodiment, the Al-C MMC fastener has an electrical conductivity greater than about 50% IACS, a UTS greater than about 120 MPa, and an elongation greater than about 10%. Fasteners having such properties may be in an extruded state, a cold worked state, or a cold worked and annealed state.

[0038] In another embodiment, the Al-C MMC fastener has an electrical conductivity greater than about 50% IACS, a UTS greater than about 200 MPa, and an elongation greater than about 3%. Fasteners having such properties are typically in the cold worked or cold worked and annealed condition.

[0039] In another embodiment, the Al-C MMC fastener has an electrical conductivity greater than about 50% IACS, a UTS greater than about 300 MPa, and an elongation greater than about 1%. Fasteners having such properties are typically in the cold worked or cold worked and annealed condition.

[0040] In a preferred embodiment, the Al—C MMC fastener has an electrical conductivity greater than about 55% or greater than about 58% IACS, a UTS greater than about 180 MPa, and an elongation greater than about 10% in the cold worked or cold worked and annealed condition.

[0041] In an embodiment, the Al-C MMC fastener has superior creep resistance compared to fasteners made from commercial aluminum alloys (e.g., 6000 series alloys). After testing at 150°C for 100 hours, the Al-C MMC fastener typically exhibits less than about 5% or less than about 1% total displacement with an applied tensile stress equal to 80% of the room temperature yield strength of the fastener. After testing at 150°C for 500 hours, the Al-C MMC fastener typically exhibits less than about 5% or less than about 3% total creep with an applied tensile stress equal to 80% of the room temperature yield strength of the fastener.

[0042] Al-CNT MMC fasteners offer improved thermal stability, allowing use at temperatures greater than 200°C. The improved thermal stability provides high creep resistance compared to commercially available Al alloys. Thermal stability is required for fasteners to maintain the necessary pre-stretch on the connected parts, and is critical for connections in electrical applications because contact resistance is directly affected by pre-stretch. For electrical applications, the high specific electrical conductivity of Al-CNT is about 60% IACS, compared to about 52% IACS for 6000 series alloys, which provides an additional advantage.

[0043] Preparation details

[0044] The disclosed embodiments include techniques for preparing Al-C MMC fasteners that contain a small amount of nanostructured C additives, such as CNTs, GNPs, fullerenes, and / or nanodiamonds. In some examples, the amount of nanostructured C additives is between 0.01 weight percent (wt%) and 2.0 weight percent (wt%), between 0.1 wt% and 1.0 wt%, or between 0.2 wt% and 0.8 wt%. In some embodiments, the amount of C additives is about 0.4 wt%, about 0.5 wt%, about 0.6 wt%, about 0.7 wt%, or about 0.8 wt%. The preparation of Al-C MMC fasteners can be accomplished according to different processes, including those described in the following examples.

[0045] An exemplary process 100 for preparing an MMC fastener is Figure 1 102, semi-finished MMC products are manufactured by extrusion, such as wire rods, rods or other profiles. At 104, semi-finished MMC products are optionally work-hardened by cold drawing, rolling or the like. At 106, fastener shafts and heads are formed by one or more of various technologies (such as milling, flow forming, forging, rolling, etc.). At 108, threads on the fasteners are formed by cutting, milling, rolling or other appropriate methods. This has completed the geometric formation of the fasteners. Optional heat treatment and optional surface treatment are then applied at 110 and 112, respectively.

[0046] The extrusion step 102 can be used to achieve several goals in the preparation of Al-C MMC fasteners. One goal is to prepare an extruded product of a specific shape and size. In the case where the elongation of the fastener is more valuable than the strength, these dimensions may coincide with the target final dimensions required for the fastener preparation, or in the case where cold working (e.g., drawing or rolling) is used to increase the strength while reducing the cross-sectional area to the target fastener size, the extruded dimensions may be too large. In addition to geometric goals (such as size and shape), extrusion with appropriate dies and parameters can be used to increase the homogeneity of C additions in poorly homogenized Al-C feedstock prepared by other methods.

[0047] Using extrusion to increase the homogeneity of Al-C MMC can lead to significant performance improvements in terms of strength, thermal stability, etc. Depending on the extrusion process used, the Al-MMC feedstock material can be in the form of Al-C rods, bars, pellets, compacted powder billets, etc., and if necessary, multiple passes through the extrusion process can be used to further improve homogeneity.

[0048] An optional work hardening step 104 may be performed on the Al-C MMC, involving cold drawing, rolling, or the like, to achieve the target size and dimensions required for fastener production. The process may be performed at room temperature, and if high elongation in the final fastener product is desired, the process may be performed at elevated temperatures to relieve internal stresses, as residual stresses from cold working will generally reduce elongation and increase strength. As an alternative to hot rolling, heat treatment may also be applied after cold rolling as a method of relieving residual stresses after production.

[0049] As part of fastener preparation, a forming step 106 is performed on the semi-finished Al-C MMC product. For example, the head and / or shaft of the fastener are created by milling, flow forming, forging, rolling or other suitable techniques. The ease of forming will depend on the structure and amount of C included in the MMC, as well as the grain size and amount of residual stress present in the material when forming. For the best forming performance of any particular Al-C MMC, care should be taken to avoid cold working by preparing the material close to the final size, or by annealing at a sufficiently high temperature to relieve the stress accumulated in the cold working process, thereby reducing the residual stress during forming. However, if the strengthening provided by the residual stress is necessary for the characteristics of the final fastener application, some forming can still be performed with little or no annealing.

[0050] The fastener threads are formed via machining or forming techniques in step 108. Examples of machining techniques include cutting, milling, or the like. Examples of forming techniques include rolling, forging, or the like. Forming processes are generally more preferred if possible. In the case of low-volume manufacturing, or if the fastener geometry requires sharp edges or other features that are difficult or impossible to use in a forming process, a machining step may be employed.

[0051] An optional heat treatment step 108 may be employed to impart desired mechanical, thermal, and / or electrical properties to the finished fastener product. For example, an annealing heat treatment may be used to increase the thermal stability of the product. Such heat treatments may impart other desired properties, such as higher elongation, higher electrical conductivity, etc. Heat treatments may also be employed to reduce residual stresses that build up in the product during various forming and / or machining steps in the manufacturing process.

[0052] An optional surface treatment step 110 may be employed to impart desired surface properties to the finished fastener product. For example, a plating or coating may be applied for corrosion resistance, improved wear resistance, or for lubrication.

[0053] Fastener Geometry

[0054] Figure 2 A general view of an example fastener is shown in FIG, but various geometries of the fastener are within the scope of the disclosed embodiments. Depending on the application, the diameter of the shaft of the fastener may be, for example, between 2 mm and 16 mm. The fastener may follow metric standards, imperial standards, or any other specification. The length of the fastener shaft may vary, for example, from 5 mm to 50 mm, to allow fastening of various components with different thicknesses. The threads may cover the entire shaft, or only a portion of the shaft.

[0055] The head of a fastener can be varied to accommodate geometric requirements, to allow for easier or less easy removal, or to adjust the contact area of ​​the fastener with the top of the component being fastened. Variations in head design can include changing the overall style. Some possible head styles include: tie-down, recessed, countersunk, flat, hexagonal, oval, disc, round, square, truss, and torque and any variation of these styles. Fastener heads can be designed to interface with and be fastened by a variety of tools, including torque wrenches, standard wrenches, Allen keys, various types and shapes of screwdrivers (e.g., Phillips), and specialized tool sets designed to prevent unauthorized removal.

[0056] Example of Al-C MMC properties without significant residual stresses

[0057] A. Strength and elongation behavior of extruded Al-CNT MMC

[0058] Figure 3 is a graph showing the beneficial physical properties of Al-0.5wt% CNT (Al-CNTMMC) in extruded state and Al-0.75wt% CNT in extruded and stretched state compared to the properties of pure Al in extruded state. More specifically, Figure 3 Tensile testing was included, which showed the properties of as-extruded Al-0.5% CNT rods with a diameter of 8.3 mm, with a UTS of about 120 MPa and an elongation of about 24%. Figure 3 Also shown are the properties of an extruded and cold drawn Al-0.75% CNT rod with a diameter of 8.3 mm, a UTS of about 185 MPa, and an elongation of about 10%. In contrast, the extruded pure Al busbar shows a UTS of about 52 MPa and an elongation of about 29%. The UTS of the extruded MMC busbar of about 120 MPa is higher than the UTS of many common Al conductors in the soft state (e.g., Al-1350-O with a UTS of about 60 MPa). The UTS of the extruded and cold drawn MMC busbar of about 185 MPa is similar to or higher than the UTS of many 6000 series Al alloys used for electrical applications.

[0059] B. Conductivity of extruded Al-CNT MMC

[0060] The conductivity of the as-extruded Al-0.5 wt % CNT MMC measured on wire samples prepared in several different production runs was consistently in the range of 59.5% to 60.5% IACS.

[0061] C. Creep behavior of extruded Al-CNT MMC

[0062] Figure 4 The results of creep tests performed on Al-0.75wt%CNT samples are shown, as well as the results of creep tests performed on Al6101-T6 alloy samples, A6063-T5 Al alloy samples, and pure Al (Al99.7) samples for comparison. The test was performed at 150 ° C, and the samples were loaded to 80% of their respective room temperature yield strengths. As shown, Al-CNT MMC has improved creep properties. Before the test was interrupted at 500 hours, the third creep stage was not reached in Al-0.75wt%CNT, while the 6063 alloy sample failed completely after about 4 hours, the 6101 sample failed after about 15 hours, and the pure Al sample failed after less than 1 hour.

[0063] Example of Al-C MMC properties after cold working to increase residual stresses

[0064] A. Strength and elongation behavior of cold-worked Al-CNT MMC

[0065] The initial extrusion diameter of the Al-CNT rod and the final diameter of the wire for the desired ultimate strength (UTS) can be calculated according to the following relationship:

[0066]

[0067] Wherein, and are constants depending on the amount of CNTs. For MMC with a nominal 0.5 wt% CNT content, and may be about 274 and 34, respectively.

[0068] Figure 5 is a graph showing how cold working affects the strength of Al-0.5wt% CNT MMC and Al round wire as the cross-sectional area decreases. More specifically, Figure 5 Shown is the strength improvement plotted with increasing cold working (wire drawing) for Al-0.5wt% CNT and Al wires.

[0069] Based on these data, strengths up to about 335MPa were observed in Al-0.5wt%CNT MMCs with sufficient cold working area reduction. In contrast, pure Al wires initially increase in strength with cold working, but the rate is reduced to some extent compared to MMC. In addition, the UTS of pure Al wires reaches a plateau at about 140MPa. Under all levels of cold working, the elongation of MMC remains consistent at 3% to 5%. This performance does not change significantly when the material is used for busbar applications rather than wires. As an alternative to area reduction, processes that apply internal stress without changing the cross-sectional area (ECAP, etc.) can be used to increase the strength of busbars initially prepared at or near the final target size.

[0070] B. Conductivity of Cold-Worked Al-CNT MMC

[0071] The conductivity of the cold worked Al-CNT wires was observed to be in a similar range as the wires before cold working was applied, 59% to 60.5% IACS.

[0072] C. Thermal stability of cold-worked Al-CNT MMC

[0073] To estimate the thermal stability of Al-CNT MMC products, heat treatment for AT4 classification (the highest classification of thermal stability described in specification IEC 62004) was applied to drawn Al 0.5wt% CNT wires with two different levels of applied cold work (85% and 98% cross-sectional area reduction). Aluminum-based materials that meet the AT4 classification are capable of continuous operation at 230°C for 40 years. To comply with AT4 thermal stability, the wires must retain more than 90% of the UTS after being held at 310°C for 400 hours. They must also retain more than 90% of the UTS after being held at 400°C for 1 hour. Figure 6As shown, both drawn Al-0.5wt% CNT wires passed this test, demonstrating excellent thermal stability. This behavior extends to fastener applications if similar levels of cold working are applied.

[0074] For certain applications, Al-CNT MMC fasteners that meet the less stringent AT3 standard for thermal stability described in IEC62004 may be sufficient while still providing substantially better performance than commercially available aluminum alloy fasteners. To comply with AT3, wire specimens must maintain more than 90% of UTS after being held at 280°C for 1 hour, or at 240°C for 400 hours. Having shown that the Al-CNT MMCs disclosed herein meet the more stringent AT4 standard, it is also apparent that the MMC products also meet the less stringent AT3 standard.

[0075] Example of improving the homogeneity of carbon addition in Al-C MMC

[0076] A. Improving the homogeneity of Al-CNT MMC by extrusion process

[0077] Figure 7 Included are images showing the difference in microstructuring between two Al 0.5wt% CNT MMCs before and after enhancement by an extrusion process. The figure shows the improvement in CNT distribution with solid state reprocessing. In the initial MMC 702, agglomerated CNTs are visible as spots in the image. After the extrusion process 704, the number and size of large visible spots decreases while the measured C content remains consistent. More specifically, Figure 7 The images are cross-sectional micrographs of Al-0.5wt%CNT MMC wires with high levels of undesirable CNT agglomeration before (702) and after (704) the addition extrusion process for increasing CNT homogeneity. The visible spots are CNT agglomerates, and the size and number density of these spots are significantly reduced with the extrusion process, indicating that the process breaks up the agglomerates and distributes the CNTs more evenly. Carbon concentration measurements confirm that the C content of these MMCs remains unchanged through the process. Therefore, it is expected that the same amount of CNTs are present in both. Relative to this observation and other observations, it is obvious that, through the extrusion process, large CNT agglomerates are broken up and CNTs are more evenly distributed. As described below, this has several beneficial effects on the properties of the MMC.

[0078] B. Improvement of thermal stability of Al-CNT MMC

[0079] Improving the homogeneity of CNT distribution within Al-CNT MMC also improves thermal stability. For example, Figure 8Shown is how heat treatment (i.e., annealing) of a drawn Al-0.5wt% CNT MMC wire containing visible CNT agglomerates affects grain size compared to a second drawn Al-0.5wt% CNT MMC wire with a more homogenous CNT distribution. In samples with poorly dispersed CNTs, grain growth occurs uninhibitedly in some areas of the sample, while other areas resist grain growth. This is due to pocket regions in the MMC with relatively low or absent CNTs, which have thermal stability similar to pure Al. This phenomenon was not observed in samples with a more uniformly distributed CNT content (e.g., smaller / fewer CNT agglomerates with the same C content).

[0080] More specifically, Figure 8 Electron beam backscatter diffraction (EBSD) images of Al-CNT MMC grains are shown, demonstrating the benefits of a uniform CNT distribution in a drawn Al 0.5wt% CNT MMC wire, as opposed to a less uniform CNT distribution. The poorly dispersed sample (802) has a larger initial grain size and exhibits a non-uniform CNT distribution and excessive grain growth as it is drawn and annealed. When subjected to the same cold working and heat treatment, the sample (804) with a more uniform CNT distribution exhibits a smaller initial grain size and maintains a relatively consistent and uniform grain size throughout the sample. As a result of the poorly dispersed CNTs in the Al-0.5wt% CNT sample, the grains grow freely without hindrance in certain internal regions, and therefore the properties of this sample are significantly less thermally stable than those in the Al-0.5wt% CNT sample with a more uniformly dispersed CNT.

[0081] Fig. 9 It is shown that Al-CNT MMCs with poor CNT distribution fail the AT4 test according to IEC 62004, while samples with a more homogeneous CNT distribution succeed (see e.g. Figure 6 and related text). More specifically, Fig. 9 A graph comparing the thermal stability of a drawn Al-0.5 wt% CNT MMC wire with poor CNT distribution and a drawn Al-0.5 wt% CNT MMC wire with a more homogenous CNT distribution is shown. Figure 6 As shown, the sample needs to maintain >90% of its initial UTS to meet AT4 thermal stability. Poorly distributed CNT samples do not pass AT4 thermal stability. This comparison emphasizes the importance of breaking up CNT agglomerates in Al-CNT MMCs to achieve their full potential.

[0082] Example of Al-CNT MMC fastener properties compared to steel fasteners

[0083] Fig. 10Aand Fig. 10B A setup for a simulation of an electrical transmission assembly for busbar to busbar connections is shown. Such connections exist in high power electrical applications, such as in battery connectors for automotive applications. In such applications, aluminum components are beneficial over currently used copper components due to the significant potential for cost and weight reduction. The demand for a wide performance range regarding the ampacity of these conductors and connectors requires high thermal stability of the connection system, due to resistive heating that occurs under high electrical loads. Due to the difference in thermal expansion between the aluminum busbars and the steel fasteners, the use of ordinary steel fasteners for these connections produces unstable connection conditions at elevated temperatures. In addition, steel has a much lower electrical conductivity than copper, about 3% to 15% IACS. Therefore, connections formed by steel fasteners may result in hot spots due to loose connections and low conductivity.

[0084] Fig.11 is a graph showing a comparison of the pre-stretch loss in a busbar to busbar connection for an aluminum busbar in combination with stainless steel fasteners versus a connection consisting of an Al-CNT MMC busbar in combination with Al-CNT MMC fasteners. The connection system was installed at 20°C with a set-up time of 1 hour. After set-up, the specimens were exposed to thermal cycles from 20°C to 200°C and back to 20°C. The dwell time at 200°C for each cycle was 100 hours, and five cycles were performed. After each cycle, the remaining connection pre-stretch was determined.

[0085] Due to the high thermal stability (e.g., AT3 or even AT4 grade) and equal thermal expansion in all-aluminum (MMC) connections, the measured pre-stretch loss is in the range of 30% of the initial installed pre-stretch. In the case of an aluminum busbar connected by a steel fastener, the pre-stretch drops by almost 90% after the first thermal cycle. This significant drop negates the high initial pre-stretch that can be applied to the more robust steel fasteners. Further high temperature exposure results in a continued loss of pre-stretch, up to an undefined low pre-stretch. Therefore, this direct comparison shows the potential for reliable electrical connections by utilizing Al-CNTMMC fasteners with aluminum-based conductors such as busbars.

[0086] Remark

[0087] The above description and accompanying drawings are illustrative and should not be construed as limiting. Many specific details are described to provide a thorough understanding of the present disclosure. However, in some cases, well-known details are not described to avoid obscuring the description. In addition, various modifications may be made without departing from the scope of the embodiments.

[0088] Reference in the specification to "one embodiment" or "an embodiment" means that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present disclosure. The phrase "in one embodiment" appearing in various places in the specification does not necessarily all refer to the same embodiment, nor does it necessarily refer to separate or alternative embodiments that are mutually exclusive of other embodiments. In addition, various features are described that may be exhibited by some embodiments and not by other embodiments. Similarly, various requirements are described that may be requirements of some embodiments and not by other embodiments.

[0089] The terms used in this specification generally have their ordinary meaning in the art within the context of the present disclosure and in the specific context in which each term is used. Certain terms used to describe the present disclosure are discussed above or elsewhere in the specification to provide additional guidance to practitioners regarding the description of the present disclosure. It should be understood that the same thing can be described in more than one way. For example, people will recognize that a "screw" is a form of a "fastener" and that these terms are sometimes used interchangeably.

[0090] Alternative language and synonyms may be used for any one or more terms discussed herein, and have no special meaning whether or not the terms are described or discussed in detail herein. Synonyms for certain terms are provided. The statement of one or more synonyms does not exclude the use of other synonyms. The examples used anywhere in this specification, including the examples of any terms discussed herein, are illustrative only and are not intended to further limit the scope and meaning of the present disclosure or any exemplary terms. Likewise, the present disclosure is not limited to the various embodiments given in this specification.

[0091] Without intending to further limit the scope of the present disclosure, examples of instruments, devices, methods and related results thereof according to embodiments of the present disclosure are given above. Note that for the convenience of the reader, titles or subtitles may be used in the examples, but this should in no way limit the scope of the present disclosure. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present disclosure belongs. In the event of a conflict, this document (including definitions) shall prevail.

[0092] From the foregoing it will be appreciated that specific embodiments of the invention have been described herein for purposes of illustration, but that various modifications may be made without departing from the scope of the invention. Accordingly, the invention is not to be limited by the appended claims.

Claims

1. A fastener configured for use in power distribution applications, the fastener comprising: Aluminum (Al) metal matrix composite (MMC) comprising nano-sized carbon particles at a concentration of 0.01 weight percent (wt%) to 2 wt%, The nano-scale carbon particles are uniformly distributed throughout the Al-MMC. 2 . The fastener according to claim 1 , wherein the concentration of the nano-sized carbon particles is in the range of 0.1 wt % to 1 wt %. 3 . The fastener of claim 1 , wherein the concentration of the nano-sized carbon particles is in a range of 0.2 wt % to 0.8 wt %.

4. The fastener of claim 1, wherein the nanoscale carbon particles comprise single-walled carbon nanotubes (CNTs).

5. The fastener of claim 1, wherein the nanoscale carbon particles comprise multi-walled CNTs.

6. The fastener of claim 1, wherein the nanoscale carbon particles comprise graphene nanoplatelets (GNPs), fullerenes, nanodiamonds, or any combination thereof.

7. The fastener according to claim 1, wherein the nano-scale carbon particles include 2 or sp 3 Carbon nanoparticles.

8. The fastener of claim 1, wherein the nanoscale carbon particles are selected from the group consisting of: CNT, GNP, Fullerenes, Nano diamond, With mainly sp 2 or sp 3 Carbon nanoparticles, and Any combination of them.

9. The fastener of any one of claims 1 to 8, wherein the fastener has an electrical conductivity greater than 50% International Annealed Copper Standard (IACS), an Ultimate Tensile Strength (UTS) greater than 80 MPa, and an elongation greater than 30%.

10. The fastener of claims 1 to 8, wherein the fastener has an electrical conductivity greater than 50% IACS, a UTS greater than 120 MPa, and an elongation greater than 10%.

11. The fastener of any one of claims 1 to 8, wherein the fastener has an electrical conductivity greater than 50% IACS, a UTS greater than 200 MPa, and an elongation greater than 3%.

12. The fastener of claims 1 to 8, wherein the fastener has an electrical conductivity greater than 50% IACS, a UTS greater than 300 MPa, and an elongation greater than 1%.

13. The fastener of any one of claims 1 to 8, wherein after heating the fastener at 400°C for 1 hour or at 310°C for 400 hours, the UTS is at least 90% of its UTS before heating.

14. The fastener of any one of claims 1 to 8, wherein the fastener shows less than 5% total displacement after creep testing at 150°C for 100 hours with an applied load of 80% of its room temperature yield strength.

15. The fastener of any one of claims 1 to 8, wherein the fastener shows less than 5% total displacement after creep testing at 150°C for 500 hours with a load of 80% of its room temperature yield strength.

16. The fastener of any one of claims 1 to 8, wherein the power distribution application comprises an automotive application.

17. The fastener according to any one of claims 1 to 8, wherein: The fastener is a bolt having a shaft diameter in the range of 2 mm to 16 mm.

18. The fastener according to any one of claims 1 to 8, wherein: The fastener is a bolt having a shaft diameter in the range of 6 mm to 8 mm.

19. The fastener according to any one of claims 1 to 8, wherein: The fastener is a bolt having a shaft length in the range of 5 mm to 50 mm.

20. The fastener according to any one of claims 1 to 8, wherein: The fastener is a bolt having a head style selected from or associated with any of the following: Bundles, Concave planer, Bury your head, Flat, hexagon, Oval, Disc, Round, square, trusses, and Torque.

21. The fastener according to any one of claims 1 to 8, wherein: The fastener comprises a bolt designed to be tightened using any of the following tools: Torque wrench, Allen key, Standard, Phillips, or special screwdriver, and A tool set is configured to prevent unauthorized disassembly.

22. An assembly for electrical transmission, the assembly comprising a fastener and a conductor according to any one of claims 1 to 21, wherein: The conductor is composed of pure Al, Al alloy or Al-C MMC.

23. The assembly of claim 22, wherein: The conductor is a busbar, a wire or a cable.

24. A method for obtaining a uniform distribution of nanoscale carbon particles throughout a metal matrix composite (MMC) fastener, the method comprising: obtaining an MMC raw material including a metal matrix and nano-scale carbon particles; as well as During or before the preparation of the MMC fastener, the MMC raw material is processed by a solid state deformation process to form the following MMC fastener: wherein the nano-scale carbon particles are uniformly distributed throughout the MMC fastener.

25. The method of claim 24, wherein the solid state deformation process comprises an extrusion process.

26. The method of claim 24, wherein the solid state deformation process comprises an equal channel angular pressing (ECAP) process.

27. The method according to any one of claims 24 to 26, wherein the MMC feedstock material is an Al-MMC feedstock material.

Citation Information

Cited By

  • Preparation method of solid solution oxygen reinforced Ti15Zr alloy with ultra-fine grain structure

    CN119614928A